Gold carbonyl cations and beyond: homoleptic gold(I) complexes with P4 and P4S3 and the half-sandwich cation (Au(C6H6)(CO))+ - Schmitt, Manuel; Nestle, Sarah; Radtke, Valentin; Krossing, Ingo (Chemical communications, 2024)
Oxidation of Au0 with the synergistic Ag+/0.5 I2 system in the commercial organic solvent 1,2,3,4-tetrafluorobenzene led to the perfluoroalkoxyaluminate salt of the [Au(CO)2]+ cation known from superacid chemistry. This [Au(CO)2]+ salt proved to be an excellent ‘naked’ Au+-synthon yielding complex salts with [Au(η2-P4)2]+, [Au(η1-P4S3)2]+ and half-sandwich [Au(η2-C6H6)(CO)]+ cation.
Gesehen am 09.08.2024
Im Titel erscheint die chemische Formel in eckigen Klammern, alle Zahlen sind tiefgestellt, das "+" hochgestellt